AGENCY BANKING, MOBILE MONEY OPERATION AND BANK PERFORMANCE IN BENUE STATE, NIGERIA - Peter Ngbede, AJAM (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study will examine agency banking, mobile money operation and bank performance in Benue State. Three proxies of agency banking namely; point of sale, mobile telephone banking and automated teller machine card usage were examined to see their effects on the performance of deposit money banks in the study area. The study adopted survey design and used structured questionnaire for data collection. The population and sample of the study consist 1,350 management staff and registered mobile money agents in the study area. A purposive sampling was used to select the elements to be used for the study. The instrument of data collection was subjected to content and construct validity while the reliability of the instrument was tested using Cronbach’s Alpha statistics. Descriptive statistics was used analyze descriptive data while multiple regression analysis was used to estimate the effect of the independent variables on the dependent variable of the study. The major finding from the study indicates that point of sales and mobile telephone banking have positive and significant effects on bank performance in the study area. It was recommended among others that deposit money banks need to improve in their operations to ensure a deeper penetration into the rural area. The study has contributed significantly to the ongoing debate of the role of agency banking on financial inclusion and bank performance in the study area.